2012
DOI: 10.1017/s1755267211000972
|View full text |Cite
|
Sign up to set email alerts
|

Record of Ellisella paraplexauroides (Anthozoa: Alcyonacea: Ellisellidae) in Italian waters (Mediterranean Sea)

Abstract: The occurrence of the candelabrum coral Ellisella paraplexauroides in Italian waters (Sicily Strait, Mediterranean Sea), was documented during a remotely operated vehicle cruise, carried out by ISPRA in May 2010 on-board the RV 'Astrea'. Five specimens were photographed and sampled from 80 to 94 m depth on the north-east coasts of Pantelleria Island, confirming the distribution of this species in the central Mediterranean Sea. A description of the living colonies and other taxonomic and ecological characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…This is probably because its typical bathymetric distribution (70–200 m) was very understudied in the Mediterranean until recently, being inaccessible to recreational scuba divers but too shallow for oceanographic campaigns (Orejas et al, 2019). Only recently, the availability of new high‐performance technologies at affordable costs and the development of technical diving allowed the study of these environments (Angiolillo et al, 2012; Giusti et al, 2012; Giusti et al, 2015; Kahng, Copus & Wagner, 2017). In fact, 13 of the 19 reports presented in this study were recorded by ROV or by technical divers.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because its typical bathymetric distribution (70–200 m) was very understudied in the Mediterranean until recently, being inaccessible to recreational scuba divers but too shallow for oceanographic campaigns (Orejas et al, 2019). Only recently, the availability of new high‐performance technologies at affordable costs and the development of technical diving allowed the study of these environments (Angiolillo et al, 2012; Giusti et al, 2012; Giusti et al, 2015; Kahng, Copus & Wagner, 2017). In fact, 13 of the 19 reports presented in this study were recorded by ROV or by technical divers.…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean mesophotic zone encompasses: i) various geomorphological zone and/or features (Gori et al 2017), like deep coastal areas (e.g. Cerrano et al 2010;Angiolillo et al 2012;Ledoux et al 2015;Fava et al 2016;Capdevila et al 2018;Idan et al 2018;Ponti et al 2018;Chimienti et al 2018b;Corriero et al 2019), continental shelf (e.g. Bo et al 2009;Salvati et al 2010;Bianchelli Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…with the use of Remotely Operated Vehicles (ROVs) or technical diving, are much more recent. These studies, carried out using direct observational techniques, revealed the great species richness of the Mediterranean deep rocky circa-littoral environments which are characterized by a large variety and abundance of sponges and corals [4] , [5] , [7] , [8] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . Among these biocoenoses, large benthic cnidarians can play an important ecological role; they are considered ecosystem engineers, creating complex three-dimensional habitats, sustaining high biodiversity levels and promoting high levels of functioning in both epi-benthic and proximal interstitial surroundings [7] , [23] .…”
Section: Introductionmentioning
confidence: 99%